2018
DOI: 10.1038/s41388-018-0297-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of apoptosis proteins (IAPs) mediate collagen type XI alpha 1-driven cisplatin resistance in ovarian cancer

Abstract: Although, cisplatin resistance is a major challenge in the treatment of ovarian cancer, the precise mechanisms underlying cisplatin resistance are not fully understood. Collagen type XI alpha 1 (COL11A1), a gene encoding a minor fibrillar collagen of the extracellular matrix, is identified as one of the most upregulated genes in cisplatin-resistant ovarian cancer and recurrent ovarian cancer. However, the exact functions of COL11A1 in cisplatin resistance are unknown. Here we demonstrate that COL11A1 binds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 48 publications
5
95
0
Order By: Relevance
“…Nevertheless, DDR2 activated by collagen was not conducive to Src homolog 2 domain phosphorylation [48]. Notably, the binding of COL11A1 to both α1β1 integrin and DDR2 to activate the Src-phosphatidylinositol 3-kinase (PI3K)/AKT-NFκB signaling pathways induced the expression of three cisplatin-induced apoptosis inhibitors in ovarian cancer [49].…”
Section: The Influence Of Collagen On Cancer Cell Behaviormentioning
confidence: 99%
“…Nevertheless, DDR2 activated by collagen was not conducive to Src homolog 2 domain phosphorylation [48]. Notably, the binding of COL11A1 to both α1β1 integrin and DDR2 to activate the Src-phosphatidylinositol 3-kinase (PI3K)/AKT-NFκB signaling pathways induced the expression of three cisplatin-induced apoptosis inhibitors in ovarian cancer [49].…”
Section: The Influence Of Collagen On Cancer Cell Behaviormentioning
confidence: 99%
“…Cancer cells were serum starved overnight prior to the experiments. Tissue culture plates were coated with 5 µg/ ml of type I collagen (COL1; Gibco Life Technologies) or COL11A1 extracted from A204-scrambled cells or A204 shCOL11A1 cells 31 (Fig. S1B) for 2 h at 37°C.…”
Section: Cell Culturementioning
confidence: 99%
“…Cancer cells were trypsinized, resuspended in 1% FBS containing medium and cultured in collagen-coated plates for 72 h before the analysis. For co-culture, CAFs were seeded in 6-well inserts (Falcon #353090) and ovarian cancer cells were plated in the companion 6-well plates (Falcon #353502) in media supplemented with 1% FBS for 72 h. CAFs have been shown to express high levels of COL11A1 and co-culture with these CAFs increased cisplatin resistance in ovarian cancer cell lines 25,27,31 . For drug treatments, cancer cells were serum starved and plated on COL11A1 extract for 48 h in media containing 1% FBS and treated with drugs (dasatinib, LY294002, MK2206 and dorsomorphin) for another 48 h. For cisplatin treatment, cancer cells were serum starved and cultured on uncoated plates, COL11A1-positive extract or COL11A1-negative extract in media containing 1% FBS for 24 h and treated with cisplatin for another 72 h.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of DDR2 is associated with breast cancer recurrence through activation of the Erk/Snail 2 pathway (Ren et al 2013, 2). In a recent study, binding of collagen 1A to integrins and DDR2 was shown to activate the Src-PI3K/Akt-NFκB signaling pathway, allowing the expression of apoptosisinhibiting proteins (Rada et al 2018). Thus, cisplatin-induced apoptosis was shown to be inhibited in ovarian cancer cells in vitro and in vivo (Rada et al 2018).…”
Section: Introductionmentioning
confidence: 99%